Solution of the Horizon Problem - Schöneberg, Philipp; Carmesin, Hans-Otto Gerhard (PhyDid B - Didaktik der Physik - Beiträge zur DPG-Frühjahrstagung, 2021)
In our article we will show a solution for the horizon problem. The problem is known since 1970. It´s about the question how the light waves could thermalize the hole expanding universe since the big bang. Our solution will use calculations, diagrams and a new self-designed time evolution. We had shown this time evolution in the article “Solution of a Density Problem in the Early Universe” out of the journal PhyDid B pp. 43-46 (spring conference 2020). In this time evolution we use dimensional transitions, which are connected to the size of the universe. So it also is connected to the distance which has to be reached from the light. With those methods we can explain how the early big dimensions could take care for the small distances and how the light was able to thermalize the space within horizon.